Comprensión lectora en estudiantes de 4° grado de primaria de asentamientos humanos y zona urbana - Red N° 9 Callao - Mendoza Valdivia, Lina (2011)
The research objective is to compare and differences between students reading comprehension in grade 4 of elementary school , in urban areas and schools in less developed areas Such as the group number 09 of Callao, also considering age and sexes. The comparative descriptive study of reading comprehension in two groups of students establishing common and differential characteristics of each. We used the Linguistic Complexity Progressive Reading Comprehension Test (CLP Grade 4 - form A). Collectively applied. Non-probability sample comprised of 315 intentional students. As a result it was found that there are significant differences in reading comprehension between grade 4 students from urban and schools in less developed areas. Considering the variable sexes differences were observed in women who were rated high. In the age variable, 9-year students have higher scores. It was evident that most students only perform less complex reading comprehension.The research objective is to compare and differences between students reading comprehension in grade 4 of elementary school , in urban areas and schools in less developed areas Such as the group number 09 of Callao, also considering age and sexes. The comparative descriptive study of reading comprehension in two groups of students establishing common and differential characteristics of each. We used the Linguistic Complexity Progressive Reading Comprehension Test (CLP Grade 4 - form A). Collectively applied. Non-probability sample comprised of 315 intentional students. As a result it was found that there are significant differences in reading comprehension between grade 4 students from urban and schools in less developed areas. Considering the variable sexes differences were observed in women who were rated high. In the age variable, 9-year students have higher scores. It was evident that most students only perform less complex reading comprehension.